Electric camera sensor vs. virtual reality archery: Which is more effective for improving archery accuracy? - Prasetyo, Yudik; Yachsie, Betrix Teofa Perkasa Wibafied Billy; Prasetyo, Heru; Shahril, Mohd Izwan bin (Journal Sport Area, 2025)
Background: The integration of technology into archery training has gained attention, yet limited studies have compared the effectiveness of electric camera sensors and virtual reality (VR) systems in enhancing archery accuracy. The lack of clear data regarding how each method impacts arrow speed and accuracy necessitates further investigation. Research Objectives: This study aims to compare the effectiveness of two training approaches—electric camera sensor-based training and VR archery—in improving arrow accuracy and speed, and to evaluate their implications for bow performance and technique assessment. Methods: A quantitative experimental design with a two-group pretest-posttest approach was employed. The study involved 20 male archers aged 15-20 years, selected via purposive sampling. Participants underwent 18 training sessions using a fixed shooting distance of 40 meters. Data were collected on arrow accuracy and analyzed using paired and independent t-tests. Finding/Results: The study found that both training methods significantly improved archery accuracy. However, athletes who trained using the electric camera sensor showed slightly greater improvements than those using virtual reality. The sensor-based training provided more precise feedback on arrow speed and trajectory, which enhanced technique evaluation and led to better shooting outcomes. These results highlight the sensor’s potential as a more effective tool for refining archery performance. Conclusion: Fixed-distance training using an electric camera sensor system is more effective than virtual reality archery in enhancing archery accuracy. The integration of arrow speed motion sensors facilitates more precise evaluations of bow technique and performance, particularly when inconsistencies in arrow trajectory occur. It is recommended for archers seeking improvements in accuracy to incorporate electric camera sensor technology into their training.